Tissue Engineering in Stomatology: A Review of Potential Approaches for Oral Disease Treatments - Cao, Lilan; Su, Huiying; Si, Mengying; Xu, Jing; Chang, Xin; Lv, Jiajia; Zhai, Yuankun (Frontiers in Bioengineering and Biotechnology, 2021)
Tissue engineering is an emerging discipline that combines engineering and life sciences. It can construct functional biological structures in vivo or in vitro to replace native tissues or organs and minimize serious shortages of donor organs during tissue and organ reconstruction or transplantation. Organ transplantation has achieved success by using tissue-engineered heart, liver, kidney and other artificial organs, and the emergence of tissue-engineered bone also provides a new approach for the healing of human bone defects. In recent years, tissue engineering technology has gradually become an important technical method for dentistry research, and its application in stomatology-related research has also obtained impressive achievements. The purpose of this review is to summarize the research advances of tissue engineering and its application in stomatology. These aspects include tooth, periodontal, dental implant, cleft palate, oral and maxillofacial skin or mucosa, and oral and maxillofacial bone tissue engineering. In addition, this manuscript also summarizes the commonly used cells, scaffolds and growth factors in stomatology and discusses the limitations of tissue engineering in stomatology from the perspective of cells, scaffolds, and clinical applications.